FORMULASI SEDIAAN SABUN CAIR ANTISEPTIK EKSTRAK DAUN RAMBUTAN (Nephelium Lappaceum L) - Yundri Sintia Hutami; Eriska Agustin; Yulius Evan Christian (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Rambutan leaves (Nephelium Lappaceum L) come from southeast Asia where They can be found in Indonesia, the Philippines, Kalimantan, Thailand and northern Australia. Rambutan fruit skin contains terpenoids, polyphenols and flavonoids which have many benefits. Traditionally, the rambutan plant is used for various diseases. All parts of the rambutan plant have their own properties, such as rambutan leaves as an alternative treatment as an antibacterial, fruit skin to treat canker sores, roots to treat fever, seed fiber to treat diabetes mellintus, leaves to treat diarrhea and blachen hair. There are two form of bath soap liquid soap and solid soap. Solid soap is made with a saponification process between far or carboxylic acid and potassium hydroxide (KOH) (NAOH). After conducting organoleptic tests, viscosity, pH, free alkali content, foam height, irritation tests on liquid soap with concentrations of 5%, 10%, 15%, all of the above tests were found to not meet the Indonesian national standards for liquid soap. Testing was carried out for 2 weeks.